Ureterovesical Reimplantation in the Teaching Clinic of Urology and Andrology at HKM National Teaching Hospital of Cotonou: Indications, Techniques and Outcomes: About 36 Cases - AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; Sewa, Edoé Viyomé; Agounkpe, Michel; NATCHAGANDE, GILLES; SOSSA, JEAN; Yévi, Magloire; GANDAHO, Isidore; SOUMANOU, FOUAD (My University, 2018)
Introduction: The presence of an obstacle in upper urinary tract, threatens kidneys and therapeutic arsenal includes an ureterovesical reimplantation especially in the case of lower ureteral obstacles. Ureterovesical reimplantation (UVR) techniques are numerous with each of its advantages and disadvantages. In order to review indications, techniques and the outcomes of the ureterovesical reimplantation in our context of work, we made this study. Material and Method: It was a retrospective, transversal, descriptive and analytic study conducted over a period of 10 years, in the department of urology University Hospital Center Hubert Koutoukou Maga of Cotonou. Patients over 15 years of age who have had a ureterovesical relocation had been included. Results: Thirty-six files were selected. Ureterovesical relocations accounted for 1.8% of surgical procedures. The ligatures iatrogenic ureters and vesico-vaginal fistulas were the most frequently involved in 33.4% and 27.8% respectively. The ureterovesical reimplantation was performed without anti-reflux plasty at 36.1% of patients. The technique of Politano-Leadbetter had been most accomplished, in 82.6% of the cases in which anti-reflux plasty had been made. Suites had been simple in 63.9% of patients. Postoperative complications were dominated by parietal suppurations and vesicocutaneous fistulas in respectively 6 and 4 patients. Conclusion: Ureterovesical reimplantations are interventions that require from the urologist a perfect knowledge given their complexity and the emergency context in which one may be led to practice them. They answer to general principles that reduce operative morbidity.
Keywords: Ureterovesical; Reimplantation; Indications; Techniques